Mechanisms of acupuncture in the treatment of type 2 diabetes mellitus: insights from the regulation of the gut microecology - Niu, Huifang; Zhou, Minfeng; Zhou, Li; Wu, Huan; Wu, Fan; Zhu, Shuxiu; Chen, Rui; Liang, Fengxia; Zhang, Hongxing (Frontiers in Immunology, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with a complex etiology, in which gut microecological dysregulation plays a central role in disease onset and progression. Acupuncture, a non-pharmacological intervention rooted in traditional Chinese medicine, confers multi-target and systemic regulatory effects, and has been extensively applied in the prevention and management of T2DM. This review systematically examines the roles of gut microbiota dysbiosis, aberrant gut-derived metabolites, intestinal barrier dysfunction, and chronic low-grade inflammation in the pathophysiology of T2DM. It further delineates the potential mechanisms by which acupuncture indirectly mitigates T2DM through modulation of the “gut microbiota–metabolite–intestinal barrier–inflammation” axis, alongside its direct actions on insulin signaling pathways and pancreatic β-cell function. Drawing on recent advances in multi-omics technologies, this review discusses the prospects and challenges of applying acupuncture in individualized and precision treatment of T2DM, aiming to provide a conceptual framework and theoretical foundation for an integrated diabetes prevention and treatment paradigm with distinctive features of traditional Chinese medicine.